Foreign Direct Investment and it is Influence on International Trade of the Economic Growth of the Philippines - Rosda Mangindalat; Rahmat Olii (Journal of Business Technology and Economics, 2024)
This research aims to investigate the relationship between Foreign Direct Investment (FDI) and international trade on Philippine economic growth. With economic growth being a major focus in the country's development, it is important to understand the contribution of FDI and international trade to achieving the Philippines' economic growth goals. The research method used is multiple linear regression to look at the economic growth of the Philippines from 2000-2022. There are two types of variables independent and dependent variables and economic growth in the relevant time period. The data used includes time series and cross-country data to strengthen the validity of the results. The analysis finds a substantial positive coefficient indicating a positive association between labor and GDP in the Philippines. For foreign direct investment (FDI), however, a negative inverse correlation was discovered, indicating the need for additional research. Additionally, the trade variable displayed a negative coefficient, suggesting that more investigation is required to fully comprehend its influence on economic growth. According to the report, to achieve sustainable growth, policies for maximizing the benefits of trade and foreign investment on the nation's development need to be reevaluated.